PENGARUH VARIETAS DAN KONSENTRASI PUPUK MAJEMUK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA (Brassica oleracea L.) - Ainun Marliah; Nurhayati Nurhayati; Risma Riana (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT The research was aimed at determining suitable varieties and concentrations of compound fertilizer RapidGro 01 on growth and yield of cauliflower. Experiment was arranged in a randomized complete block design (RCBD) 3x3 with 3 replications. There were two factors studied, i.e. 1) varieties consisted of 3 levels (PM 126 F1, White Shot and Cauliflower Tropica 45 Days) and 2) concentration of compound fertilizer RapidGro 01 consisted of 3 levels (2, 4, and 6 gL-1of water). Results showed that varieties significantly affected plant height at 30 days after planting, leaf numbers at 45 days after transplanting (DAT) and wet weight of flowers per plant, but did not significantly affect plant height at 15 and 45 DAT, leaf numbers at 15 and 30 DAT, root length and wet weight. The best variety was AM 126 F1. Concentrations of compound fertilizer RapidGro 01 did not significantly affect plant height and leaf numbers at 15, 30, and 45 DAT, root length, fresh weight per plant and wet weight per plant. There was no significant interaction between varieties and concentrations of compound fertilizer RapidaGro 01 on all variables of growth and yield of cauliflower.